Identification of subsidence hazard zone by integrating engineering geological mapping and electrical resistivity tomography in Gunung Kidul karst area, Indonesia - Wahyu Wilopo; Doni Prakasa Eka Putra; Teuku Faisal Fathani; Slamet Widodo; Galeh Nur Indriatno Putra Pratama; Maris Setyo Nugroho; Wisnu Rachmad Prihadi (Journal of Degraded and Mining Lands Management, 2022)
The presence of natural cavities in karst morphology may cause severe civil engineering and environmental management problems. Karst formations will limit the expansion of urbanization, especially infrastructure development in limestone areas. Geophysical methods, especially electrical resistivity tomography (ERT) techniques, are effective and efficient solutions to detect voids below the surface. This study aimed to develop a subsidence hazard map as basic information for infrastructure development. The identification was made by measuring electrical resistivity tomography on eight profiles in the infrastructure development plan. In addition, it was also supported by geological mapping, particularly the structural geology and types of rocks around the site. The research area consists of massive limestone, bedded limestone, and cavity limestone with generally north-south joints. The analysis of geological mapping data and electrical resistivity tomography measurements showed that the cavity limestone was identified with a north-south elongated pattern in line with the fracture pattern found on the surface at the research area. The surface lithology type, the geological structures density, and the subsurface lithology were used to develop a subsidence hazard map. This information is beneficial in determining the safe location of infrastructure development based on disaster risk mitigation.